Qualitative Analysis of Biotechnological Process Viscosity (Global Journal of Science Frontier Research, 2012)
A mathematical model of the lyzin biosynthesis process during periodic cultivation of Brevibacterium flavum type microbial population is proposed. A parametric identification of the model's kinetic variables is carried out. As a result the evaluation of the parameter values is obtained. On the basis of the qualitative theory of ordinary differential equations a bifurcation analysis of the microbial population behaviour is done regarding the cultural medium viscosity in the plane of kinetic variables-biomass concentration and oxygen concentration. With the fjelp of the bifurcation analysis, it can be predicted whether the dissolved oxigen concentration in the 'bioreactor is larger than the critical one and the prescription of the technology' of the microorganisms cultivation is executed strictly by the cultural medium viscosity only. It is investigated theoretically at which viscosity values the specific biotechnologi- cal process can cross from unstable to stable state.
Keywords: Lyzin biosynthesis process; viscosity; kinetic variable; cultural medium; massexchange parameter; parametrical identification; qualitative analysis; p